187 Body Performance of Beef Steers Swathgrazing oat Monoculture or Forage-Blends During Winter Months. (21st September 2022) - Durunna, Obioha N; Oyedeji, Oluwatobi; Vandenberg, Carien; Krys, Deanna; Lardner, Bart
Abstract: Extended grazing strategies have the potential to reduce beef winter-feeding costs. Beef producers can incorporate monoculture cereal crops in their winter swathgrazing programs, but recently, the use of polycrops (also known as intercrops or cover crops) is growing. There is little information about beef cattle body performance when swathgrazing forage blends during winter months. This study evaluated animal performance when swathgrazing oat monoculture or a polycrop blend (oat, turnip, canola and forage pea). Forage systems (treatment) were seeded on a 12-hectare site, further separated into 2-hectare paddocks. The paddocks were seeded in June and swathed in August at the hard dough stage for the oats. Forty-two crossbred steers were randomly allocated to one of two replicated (n=3) systems while balancing for body weight and breed composition. Body weights (BW) were determined over two consecutive days at the start and end of grazing, and at 2-wk intervals throughout the 86 d grazing period. Ultrasound backfat, rumpfat and intramuscular fat were collected at the start and end of the trial. At the start of the trial, two steers in each replicate group were fitted with rumen pH/temperature boluses. The biomass yield of the oat and polycrop were 6, 225±651 and 4, 867±471 kg DM ha -1, respectively, while mean regrowth for oat and polycrop were 177 and 1409 kg DM ha -1, respectively. Start-of-test BW (246, 247kg; P = 0.92), end-of-test BW (304, 303.5; P = 0.97), average daily gain (0.68, 0.74 kg d -1 ; P = 0.61), backfat change (0.53, 0.69 mm; P =0.65), rumpfat change (0.84, 1.30 mm; P=0.14) and intramuscular fat change (-0.12, 0.14%; P=0.66) did not differ for steers assigned to oat and polycrop systems, respectively. Other measures were mean rumen temperatures (39.13 o C, 38.96 o C; P=0.03) and pH (6.76, 6.70; P=0.10) for the oat and polycrop respectively. These results suggest that polycrops may be an alternative in a swath grazing system during the winter months.